Examining the Effects of Investor Sentiment Shocks on Normal and Abnormal Returns in the Oil Products Sector of the Tehran Stock Exchange: A PVAR Analysis - Mohammad Javad Zare Bahnamiri; Samira Balavar; vahid omidi (Journal of Asset Management and Financing, 2024)
AbstractThe behavioral finance perspective posits that fluctuations in security prices are significantly influenced by investors' emotional responses, which can, in turn, affect stock returns. Understanding the sources of stock price changes is critical within asset pricing theory, highlighting the necessity of exploring the effects of investor sentiment on stock returns. This study aimed to investigate how investor sentiment shocks impact both normal and abnormal returns in the oil products sector of the Tehran Stock Exchange. To measure abnormal returns, we employed the six-factor model developed by Fama and French (2018). Investor sentiment was evaluated using the Relative Strength Index (RSI), the Psychological Line Index (PLI), trading volume, and the Adjusted Turnover Rate (ATR). Data were collected from 12 companies in the oil products industry over a period of 1,584 months, spanning from 2010 to 2020. The findings revealed that the influence of sentiment shocks on normal returns was more pronounced than on abnormal returns. Conversely, the impact of normal return shocks on sentiment was initially positive but became negative over time. Additionally, positive shocks to abnormal returns adversely affected investor sentiment, with the peak effect observed after five periods. This research enhances the understanding of how investor sentiment shocks influence normal and abnormal returns in the oil products sector, offering valuable insights into behavioral differences among investors.